DIGITAL HEALTH AND WELLNESS PLATFORMS: A MICROSERVICE-BASED ARCHITECTURE FOR INTEGRATED HEALTHCARE MANAGEMENT - Nitin Saksena, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The development of Digital Health and Wellness Platforms (DHWP) marks a radical change in systems of healthcare administration. Modern DHWPs, which provide complete one-stop solutions for health managers, coaches, nutritionists, and healthcare practitioners, are investigated together with their architectural framework and implementation. These systems deftly combine several healthcare components—including telehealth services, pharmaceutical management, electronic health records (EHR), and real-time health monitoring through wearable devices—by using microservices and event-driven design. Through safe, HIPAA-compliant technologies and gamification and reward programs, this article investigates how DHWPs enable customized health paths. Moreover, this article shows how these platforms efficiently close the distance between conventional healthcare providers and contemporary digital solutions, building a linked ecosystem that improves user interaction and health results. This architecture study offers important new perspectives on the technical basis needed to create scalable, integrated digital health systems that satisfy the changing needs of the healthcare sector.